A Study on Motivational Differences in English Oral Classes Taught by Native vs. Non-native Teachers - Qiu, Yaxuan (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of globalization, the importance of English language skills to students’ personal development and social needs has become increasingly important. Motivation is a key determinant of learning effectiveness and has a significant impact on college students’ English language skills. Compared to previous research, this study aimed to investigate the effects of native and non-native teachers on students’ motivation to learn English in the classroom. By comparing the effectiveness of the two types of teachers in stimulating students’ interest in learning and increasing their motivation, it provides insights into the similarities and differences between native and non-native-speaking teachers in teaching English as a foreign language. It finds out that the influence of foreign and native English teachers on students’ motivation to learn spoken English is multifaceted. Both foreign and native teachers can bring unique advantages to the classroom, and the choice between the two types of teachers may depend on individual factors. The combination of the two approaches has the potential to provide a well-rounded learning experience that meets the different needs and preferences of students in the spoken English classroom.